DETERMINAN OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR DI BEI TAHUN 2013-2016 - Sustari Alamsyah (Balance Vocation Accounting Journal, 2017)
The purpose of this study is to examine and analyze the influence of internalfactors such as profitability, liquidity, solvency, cash flow and corporate growth ongoing concern audit opinion. The research design is causality with the unit ofanalysis is the company of the samples taken by purposive sampling technique on thepopulation of manufacturing companies listed on the BEI year 2013-2016. Analyticaltechnique used is logistic. The results showed that simultaneously the independentvariables have an effect on the dependent variable, whereas the partial variable ofsolvency and cash flow have an effect on going concern audit opinion, andprofitability, liquidity, and company growth variables have no effect on goingconcern audit opinion.Keywords: Audit Opinion Going concern, profitability, solvency, liquidity, and cashflow